2021
DOI: 10.3390/rs13030389
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Image-Based Event Detection for Large-N Seismic Arrays Using a Convolutional Neural Network

Abstract: Passive seismic experiments have been proposed as a cost-effective and non-invasive alternative to controlled-source seismology, allowing body–wave reflections based on seismic interferometry principles to be retrieved. However, from the huge volume of the recorded ambient noise, only selected time periods (noise panels) are contributing constructively to the retrieval of reflections. We address the issue of automatic scanning of ambient noise data recorded by a large-N array in search of body–wave energy (bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In the broader context of emergency response, the significance of the damage classification output should be validated by other data sources. Seismic vulnerability reports, smart building structural monitoring [46] and earthquake magnitude measurements based on environmental noise [4] can be ancillary information to earth observation-based damage classification. The aforementioned information sources, along with ground-truth verification, should be taken into account for the response planning by the local authorities, as the traffic network capacity and the citizen mobility demands change dramatically during the recovery process [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the broader context of emergency response, the significance of the damage classification output should be validated by other data sources. Seismic vulnerability reports, smart building structural monitoring [46] and earthquake magnitude measurements based on environmental noise [4] can be ancillary information to earth observation-based damage classification. The aforementioned information sources, along with ground-truth verification, should be taken into account for the response planning by the local authorities, as the traffic network capacity and the citizen mobility demands change dramatically during the recovery process [16].…”
Section: Discussionmentioning
confidence: 99%
“…Harirchian et al [3] assess the seismic vulnerability given a set of quantifiable parameters. The regional seismicity can also be monitored using ML if the automatically captured ambient noise data are subjected to Convolutional Neural Network (CNN)-based classifiers in order to detect earthquake events [4]. In the post-disaster phase, ML approaches have been employed to locate and measure post-earthquake urban damage, confirming the relevance of this field for such kinds of applications [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to perform iterative data discovery, which results in analysis, detection, and information extraction such as popular events, is what big data most importantly permits. According to this challenge, in particularly concentrate on this work on the topic of automatic online event detection [4] on Twitter microblogs by fusing a big data analytics environment [5] with Twitter analytics to produce a novel approach that can improve event detection within the big data space. Big data demonstrated that social media data is useful for identifying data dissemination features and spotting earthquake myths.…”
Section: Introductionmentioning
confidence: 99%
“…This supplies a new option that utilizes computers to process data and enables computers to analyze and interpret it. In recent years, many efficient algorithms have been created to promote the application of ML and CV methods in structural health monitoring [14][15][16][17][18][19][20][21][22][23]. These methods effectively reduce or eliminate the dependence on professional measuring equipment, expensive sensors, and the subjective experience of inspectors.…”
Section: Introductionmentioning
confidence: 99%